Change of 7Be decay rate under compression. (December 2020) - Sikdar, A. K.; Ray, A.; Das, P.; Pathak, S.; Datta, J.
Abstract: We have studied the change of decay rate of 7 Be implanted in the small Pd lattice versus large Pb lattice. Since the electron affinities of Pd and Pb are very low and similar, any observed increase of the decay rate of 7 Be could be attributed to the compressional effect in the smaller confinement of Pd lattice. It has been found that the decay rate of 7 Be is faster in Pd lattice compared to that in Pb lattice by (0.82± 0.16)%. Similar results were observed by applying high external pressure on 7 BeO lattice. Density functional calculations underpredict the increase of 7 Be decay rate under compression by a large factor. It is important to understand this result because of its significance in calculating 7 Be decay rate in the solar core and corresponding 8 B neutrino flux.